Lost Minnesota : Stories of Vanished Places - El-Hai, Jack (Book collections on Project MUSE., 2000)
Jack El-Hais Lost Minnesota is the first book to tell the stories of buildings and landmarks from rural and small-town Minnesota, as well as those of the residential and suburban areas of the states largest cities. Lost Minnesota presents eighty-nine beautifully illustrated stories about these fascinating places and those who built them, lived in them, and tore them down. This is a book sure to delight the Minnesota history enthusiast and anyone who is curious about the states changing urban, small-town, and rural landscapes.